The Fourth Marine Brigade in World War I battalion histories based on official documents - Clark, George B. 1926- (McFarland, 2015)
"During World War I, the American Expeditionary Force Second Division saw more action and captured more ground and enemy combatants than any other. This volume follows the 4th Marine Brigade through their service in France in 1917 and 1918, their post-war occupation of Germany, and their arrival in New York City in August 1919. "..